Association between teachers' appreciation and students' performance: an analytical cross-sectional analysis - Fozia Fatima; Fuad Ahmad Siddiqi; Sabir Ali (Frontiers in Education)
The present study aimed to explore the correlation between teachers' appreciation and students' academic performance in Pakistan's postgraduate education context. A research survey served as the primary methodology for data collection. Using a random sampling technique, students from Master in Health Professions Education (MHPE), Master of Science in Nursing (MSN), and Master in Health Care Administration (HCA) from the National University of Medical Sciences were included in the sample, resulting in 150 participants, evenly split between males and females who voluntarily participated in the research. To ensure the reliability and validity of the survey instrument, a pilot testing phase was implemented. Subsequently, data obtained from the survey were analyzed using statistical methods such as Mean, Percentage, Chi-Square, t-test, ANOVA, Mann-Whitney, and Kruskal-Wallis tests. Findings revealed a significant association between teachers' appreciation and students' academic performance at the postgraduate level. Moreover, the study identified that factors such as gender, age, and academic discipline significantly influenced students' perceptions of educators' appreciation, while the distinction between public and private educational backgrounds did not yield any significant variance. Similarly, students' academic performance was significantly influenced by their background, age, and discipline, with gender exhibiting no considerable impact. Consequently, the study underscores the importance of prioritizing the behavioral and attitudinal development of teachers through comprehensive teaching development and training programs. These programs should aim to enhance educators' appreciation of students, thereby potentially fostering improved academic performance among postgraduate students.